Research on Risk Control and Regulatory Policies of Financial Institutions - Zhao, Zhuolin (International Journal of Global Economics and Management, 2024)
This paper examines the risk control and regulatory policies of financial institutions. It begins with classifying the risks faced by financial institutions and analyzes the impact of these risks on both the institutions and the broader financial system. The importance of risk control is then explored, followed by a detailed discussion of the current regulatory policies and strategies in place. Finally, the paper concludes with a summary of the research and suggestions for future study directions.